Peranan Alokasi Dana Desa (ADD) dalam Meningkatkan Pengembangan Desa - Aprilia Indah Wulandari; Retno Wulan Sekarsari; M. Mas'ud Said (Idarotuna : Journal of Administrative Science, 2025)
The Village Fund Allocation (ADD) is a financial tool offered by local governments to villages in order to promote development and empower communities, as required by Law Number 6 of 2014 on Villages. With a descriptive approach, the study adopted a qualitative method. Data were collected via in-depth interviews, field observations, and documentation. The research informants included village heads, local officials, MSME managers, and community leaders. Data analysis involved employing data reduction techniques, presenting the data, and drawing conclusions based on the principles of good governance and Village SDGs. The study’s findings indicate that Village Funds (ADD) play a significant role in fostering community development and empowerment, though the direction of their application differs based on the unique potential of each village.  Mangliawan Village directed ADD towards bolstering education and economic empowerment through traditional herbal medicine (MSMEs), leading to enhanced community income and better educational facilities. Meanwhile, Sekarpuro Village employs Village Funds (ADD) to foster historical and agricultural tourism through the management of the Sekaran Site, melon-picking tours, and catfish farming. This initiative leads to economic diversification and the establishment of a tourism-oriented village identity. Regarding governance, both villages have adopted participatory planning mechanisms and ensured budget transparency through village deliberations and information publications. Nonetheless, there are ongoing challenges, such as a shortage of human resources, slow fund disbursement, minimal community involvement, and inadequate supporting infrastructure.